Synthesis of N-Heteroarenemethyl Esters via C–C Bond Cleavage of Acyl Cyanides Under Transition Metal-Free Conditions - Lai, Miao; Su, Fangyao; Hu, Jingyi; Wang, Mengzhuo; Zhao, Mingqin; Zhang, Ganlin (Frontiers in Chemistry, 2022)
A practical method to synthesize N-heteroaryl esters from N-heteroaryl methanols with acyl cyanides via C–C bond cleavage without using any transition metal is demonstrated here. The use of Na2CO3/15-crown-5 couple enables access to a series of N-heteroaryl esters in high efficiency. This protocol is operationally simple and highly environmentally benign producing only cyanides as byproducts.